Applying the Discovery Learning Approach to Enhance Students' Reading Skills at State Islamic Senior High School 1 West Aceh (An Experimental Study): تطبيق أسلوب التعلم الاكتشافي لترقية قدرة الطلبة على مهارة القراءة في المدرسة الثانوية الإسلامية الحكومية 1 أتشيه الغربية (دراسة تجربية) - Muslimah, Hidayatil; Agusti Utami, Delian; Rani, Samsuar A.; El Zahraa, Fatima (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2025)
This study investigates the application of the discovery learning method to enhance students’ reading skills at State Islamic Senior High School 1, Western Aceh. The research was prompted by classroom observations indicating that Arabic language teachers often rely on conventional approaches, which do not adequately engage students—particularly in the context of reading instruction. As a result, students are limited to passive reception of information through teacher explanations, leading to disinterest, reduced motivation, and poor participation. These challenges highlight the need for a more interactive and student-centered learning strategy. Through a quasi-experimental design involving pre-test and post-test measures, this study demonstrates that the discovery learning method has a significant positive impact on students’ reading proficiency. Statistical analysis using a paired-sample t-test yielded a calculated t-value of 26.73, which far exceeds the critical values at both the 5% (2.09) and 1% (2.86) significance levels. Accordingly, the null hypothesis is rejected in favor of the alternative, confirming the effectiveness of discovery learning in improving reading outcomes.